HUBUNGAN ANTARA MASUKAN CAIRAN DENGAN INTERDIALYTIC WEIGHT GAINS (IDWG) PADA PASIEN CHRONIC KIDNEY DISEASES DI UNIT HEMODIALISIS RS PKU MUHAMMADIYAH YOGYAKARTA - Istanti, Yuni Permatasari (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT Background. Interdialytic Body Weight gains (IDWG) is an increase volume of liquid that is manifested by an increase in body weight as an indicator to determine the amount of fluid intake during the period interdialytic and patients adherence to fluid regulation in patients receiving hemodialysis therapy. Increased IDWG exceed 5% of dry weight can cause various complications such as hypertension, hypotension intradialysis, left heart failure, ascites, pleural effusion, congestive heart failure, even death. IDWG caused by various factors both internal factors include age, gender, educational level, thirst, Stress, Self-efficacy, as well as external factors as family, social support and fluid intake. Purpose. The purpose of this research was Â to know the correlation between fluid intake and IDWG on Chronic Kidney deseases (CKD) patients undergoing hemodialysis in the hemodialysis unit RS PKU Muhammadiyah Yogyakarta. Research Method. Descriptive analytic study with cross sectional design with 48 patients, collected from 79 hemodialysis Â patients. Result. The results showed there is significant relationship between fluid intake and IDWG (r = 0.541, p-value = 0.000). Conclusion. It was concluded that fluid intake is a significant contributing of IDWG. Keywords: Interdialytic Weight Gains (IDWG), fluid intake, Chronic Kidney Deseases (CKD)